GAME EDUKASI PENGENALAN BAHASA INDONESIA BERBASIS ANDROID UNTUK PENCARI SUAKA DI BATAM - Nopri Hidayat; Maslan, Andi (Computer Science and Industrial Engineering, 2022)
ABSTRACT An asylum seeker is a person who has applied for protection but his application is in the process of being determined. Batam is one of the cities in Indonesia that is home to asylum seekers. Asylum seekers in Batam stay at Hotel Kolekta Batam. Data for May 2022, the total number of asylum seekers staying at the Kolekta Batam hotel is 283 people. Asylum seekers from Afghanistan became the most inhabited with a total of 173 people. While living in Indonesia, the problem is communication with the surrounding community who use Indonesian, especially children. Although there are already Indonesian language learning programs, there is still a need for a more fun learning method, one of which is games. Games are more liked by children in terms of learning than using books. To overcome these problems, an Android-based Indonesian language introduction educational game was built using the MDLC method. The MDLC method is divided into several stages, namely concept, design, collecting material, assembly, testing, and distribution. This educational game has 4 sub-menus, namely: learn, play, about and exit. Educational games are accompanied by attractive designs and animations so that they are interesting to use for children to learn. Keywords: Educational Games, Asylum Seeker, Indonesian Language, Android Based.